Celebrating a Century of Women in the Law: Using Historical Exhibitions to Enhance User Engagement and Promote a Library Service. (March 2021) - Curley, Vanessa; Foley, Sarah
Abstract: In 2019 the Bar of Ireland Law Library launched an online exhibition detailing the first one hundred years of women in the law in Ireland and the first one hundred women called to the Irish Bar. The online exhibition coincided with the centenary celebrations of the Sex Disqualification (Removal) Act 1919 and a physical exhibition curated in collaboration with the Honorable Society of Kings Inns and the Law Society of Ireland. This article by Vanessa Curley and Sarah Foley explores the background to how Law Library staff became involved in creating historical exhibitions, the development of a digital archive of The Bar of Ireland and curating online exhibitions to complement this. It will also discuss the benefits of such activities to the Law Library service and the wider Bar of Ireland.